Yusuf al-Qaradawi’s View on Religious Extremism - Purwanigtyas, Dhita Ayomi; Hasanah, Zahra Uswah (Journal of Islamic and Occidental Studies, 2024)
Indonesia is a country with complex religious diversity issues. This is evidenced by the persistence of inter-religious conflicts caused by religious extremism. From within Muslims, this problem has become a discussion of scholars. Therefore, this study analyses Yusuf al-Qaradawi's concept of religious extremism to map the scattered extremist groups and avoid mistakes in assessing a group. Yusuf al-Qaradawi stated that extremism is an excessive attitude toward religion that can destroy religious communities because it causes error. In this study, the researcher used a philosophical approach, and the method used was a descriptive-analytical method to analyze Yusuf al-Qaradawi's thoughts regarding the problem of extremism in his work Al-Shaḥwah al-Islāmiyyah bayna al-Juḥūd wa al-Tatharruf. The results of this study found that according to al-Qaradawi, extremism has several factors and characteristics. In this case, al-Qaradawi also put forward the concept of “Wasathiyyah” in Islam to overcome the extremism problem, which proves the essence of Islamic teachings that bring peace and respect differences between people.